Next-Generation Sequencing of Cell-Free DNA Extracted From Pleural Effusion Supernatant: Applications and Challenges - Patel, Ami; Hissong, Erika; Rosado, Lucelina; Burkhardt, Robert; Cong, Lin; Alperstein, Susan A.; Siddiqui, Momin T.; Park, Hyeon Jin; Song, Wei; Velu, Priya D.; Rennert, Hanna; Heymann, Jonas J. (Frontiers in Medicine, 2021)
Cell-free DNA (cfDNA) extracted from diverse specimen types has emerged as a high quality substrate for molecular tumor profiling. Analytical and pre-analytical challenges in the utilization of cfDNA extracted from pleural effusion supernatant (PES) are herein characterized in patients with metastatic non-small cell lung carcinoma (NSCLC). Pleural effusion specimens containing metastatic NSCLC were collected prospectively. After ThinPrep® (TP) and cell block (CB) preparation, DNA was extracted from residual PES and analyzed by gel electrophoresis for quality and quantity. Libraries were prepared and sequenced with a targeted next-generation sequencing (NGS) platform and panel clinically validated for plasma specimens. Results were compared with DNA extracted from corresponding FFPE samples that were sequenced using institutional targeted NGS assays clinically validated for solid tumor FFPE samples. Tumor (TC) and overall cellularity (OC) were evaluated. Fourteen specimens were collected from 13 patients. Median specimen volume was 180 mL (range, 35–1,400 mL). Median TC and OC on TP slides and CB sections were comparable. Median extracted DNA concentration was 7.4 ng/μL (range, 0.1–58.0 ng/μL), with >5 ng/μL DNA extracted from 10/14 specimens (71%). Mutations were identified in 10/14 specimens, including 1/3 specimens with median molecular coverage <1,000 reads. The minimal detected allelic fraction was 0.6%. NGS was falsely negative for the presence of one driver mutation. No correlation was identified between sample volume or OC, quality or quantity of extracted DNA, or mutation detection. Despite analytical and pre-analytical challenges, PES represents a robust source of DNA for NGS.